Livestock Judging, Leaders Guide: Florida 4-H Animal Science Program - Deborah J. Glauer (EDIS)
Contains a complete, easy-to-read outline for activities which are a mix of games, experiments, role plays or demonstrations that help to teach the basic principles and concepts of livestock judging. The activities conclude with discussion questions for youth to REFLECT and APPLY.